Perceived CSR and Corporate Reputation: The Mediating Role of Employee Trust. (September 2018) - Yadav, Rama Shankar; Dash, Sanket Sunand; Chakraborty, Shreyashi; Kumar, Manoj
Executive Summary: This research article focuses on the importance of corporate social responsibility (CSR) in building corporate reputation of an organization. Scholars have studied CSR as an antecedent of corporate reputation, but the underlying mechanism of this process has been rarely explored. In order to fill this research gap, authors conducted an empirical study on 210 employees working in an automobile organization in India. The conceptual framework based on comprehensive literature review hypothesized that the perceived CSR of an organization may lead to trust development among the employees which in turn may lead to building of corporate reputation of the organization. The model was tested and all the hypotheses were accepted. Hence, it may be inferred that perceived CSR of an organization may develop a sense of trust among employees of an organization and in turn leading to the building of corporate reputation. The study has several implications for managers and scholars. The findings give a clear understanding that CSR activities of any organization can lead to trust development among employees at the same time they may aid in enhancing the corporate reputation of an organization. Hence, we suggest that in order to gain maximum benefits from CSR, managers should ensure that all the employees are aware of their firm's CSR activities. Further, managers should adopt CSR activities that have high salience among current or potential employees so that its benefits are positively impacting its stakeholders and the firm. Such CSR activities can include investments in institutions where training is imparted to the organization's workforce; organizing social welfare activities in areas close to the company's location. The study also has future research implications for researchers working in the area of CSR. Scholars can explore other mediating variables which may explain the underlying mechanism between CSR and corporate reputation. The study can also be replicated in other sectors in order to enhance the generalizability of the findings.